Analysis and improvement of gas turbine blade temperature measurement error. (18th September 2015) - Gao, Shan; Wang, Lixin; Feng, Chi; Daniel, Ketui
Abstract: Gas turbine blade components are easily damaged; they also operate in harsh high-temperature, high-pressure environments over extended durations. Therefore, ensuring that the blade temperature remains within the design limits is very important. In this study, measurement errors in turbine blade temperatures were analyzed, taking into account detector lens contamination, the reflection of environmental energy from the target surface, the effects of the combustion gas, and the emissivity of the blade surface. In this paper, each of the above sources of measurement error is discussed, and an iterative computing method for calculating blade temperature is proposed.